Modelo de Vivienda Para Familias Vulnerables Comunidad Territorio De Paz, Ibagué Tolima (2023)
Within the design and urban structuring component, we seek to respond to the social problems that arise in the "Territorio De Paz" neighborhood, located in commune 7 in the municipality of Ibagué, department of Tolima. Taking into account the recognition of the territory, important aspects were detected to evidence the current state of the sector; the conditions of the environment and the relationship with the community were analyzed, which shows urban deficiencies from the model of organic occupation or from informality, the facts of violence (Figueroa, 2021), the consumption of substances, micro-trafficking and lack of opportunities, are factors that establish a high pattern in terms of social vulnerability.